The Impact of the Construction of a Dam on Flood Management - Khaddor, Iliasse; Achab, Mohammed; Soumali, Mohamed Rida; Benjbara, Abdelkader; Alaoui, Adil Hafidi (Salehan Institute of Higher Education, 2021)
A possible strategy to mitigate the effects of flooding from an area identified as having high runoff potential will reduce the volumes of water that overflow the drainage area and build a system of a storage location in the coastal city of Tangier. The study is based on two main axes: (i) the extreme flow frequency analysis, using eight probability laws adjusted by the Maximum Likelihood method, and (ii) the estimation of the flood outflows at the dam outlet using the routing method in order to assess the effect of detention dams on water flood. Annual (Maximum) series based flood sampling procedure is adopted for constructing the Flood Frequency analysis. A numerical comparison of AIC criteria and BIC has allowed a proceeding to the selection of the most fitted law distributions. The result shows that the Gumbel law is best adapted to the predetermination of the extreme flow estimation in the Mghogha watershed for different return periods. The reservoir routing method along with rainfall-runoff processes were applied by the mean of the HEC-HMS model. The model was run under two different scenarios. Scenario 1 simulates the Mghogha basin with the absence of the reservoir. Meanwhile, scenario 2 simulates the same basin by taking into account the existence of the Ain Mechlawa reservoir within different return periods of from 2 to 200 years. Peak discharges downstream have been dramatically attenuated and water volumes have been decreased with the prolongation of the return period. For the 100 and 200 return periods, the peak discharge of flood reduction for scenario 1 and scenario 2 were 52.06 and 52.17 %, respectively, and for the flood volume was 22.46 and 22.82% respectively. Finally, the results of investigations showed a good performance of the model in the estimation of outflow peak discharge of the Ain Mechlawa Dam.Â Doi: 10.28991/cej-2021-03091658 Full Text: PDF